Effects Of Probiotics On The Growth And Survival Of Whiteleg Shrimp (Litopenaeus Vannamei) And Their Inhibitory Roles Against Vibrio Parahaemolyticus - Far, Hadi Zokaei (2009)

(untitled)
A study focused on the use of putative bacteria as probiotics to reduce nutritional and disease problems in aquaculture industry was carried out. This study was conducted in two experiments to investigate the putative bacteria flora as probiotics (isolated from Macrobrachium rosenbergii) for enhancement of growth and survival of L. vannamei in duration of 2007 to 2008 at University Putra Malaysia. In the first experiment, a feeding trial was carried out to investigate the potential probiotic properties of Bacillus subtilis isolated from M. rosenbergii on L. vannamei. Putative B. subtilis bacterium was added to commercial shrimp feed as a probiotic. Four types of diets were prepared by mixing the commercial pellet shrimp feed with; i) B. subtilis (T1), ii) mixture of B. subtilis and a commercial probiotic (T2), iii) commercial probiotic as positive control (T3), and iv) an un-supplemented feed as negative control (T4). After 60 days the shrimps fed diet mixed with B. subtilis showed the highest survival rate 75.5± 4.62 % and the greatest yield 190.00± 13.13 g and also there were significant differences (P< 0.05) for bacterial count between T1 and the other treated groups. It was found that, feed treated with B. subtilis appeared to enhance growth and survival rate of L. vannamei at concentration of 1010 CFU/g. Another experiment was carried out to investigate the potential probiotic-ability of B. subtilis to combat with the L. vannamei disease problems. After 60 days of culture, shrimps were challenged by immersion method to V. parahaemolyticus (107 CFU/ml). Four treatment groups were presented in this experiment which were; i) T1- Shrimps treated with B. subtilis in the first experiment were challenged with V. parahaemolyticus, ii) T2- Shrimps treated with mixture of B. subtilis and commercial probiotic in the first experiment were challenged with V. parahaemolyticus, iii) T3- Shrimps treated with unaltered diet were challenged with V. parahaemolyticus as negative control group, and iv) T4- Shrimps treated with commercial probiotic diet were challenged with V. parahaemolyticus as positive control group. After 15 days of the challenge test, there were no significant differences in survival rate between treatment and control groups. There was no significant mortality or disease symptoms due to infection pathogen, and survival rate for all of treatment and control groups was 100%. Another study was carried out to confirm whether V. parahaemolyticus is a pathogen. One hundred shrimp (a new group) with the same size and the same age of shrimps were prepared to confirm the pathogenicity of V. parahaemolyticus. Survival rate after 10 days was 57% due to existing mortality from V. parahaemolyticus. To find the reason of non-mortality of the negative control group during the challenge test with V. parahaemolyticus, bacteria were isolated from digestive tract, muscles and body surface of negative control group, based on morphological observation. Forty three kinds of bacteria were isolated. From these isolated bacteria, 30% were gram positive bacteria, 30% were Pseudomonas spp. and 40% were Enterobacteriacea. Antagonism tests were put for isolated Pseudomonas spp. by the cross-streak method with three pathogens; V. parahaemolyticus, V. alginolyticus, and V. cholerae. Results of antagonist test for four isolated Pseudomonas spp. bacteria showed perfect antagonistic activity against the three pathogens. Perhaps the reason for no observed mortality during the challenge test was due to availability of these natural microflora bacteria (Pseudomonas spp.) inside the body of shrimps, and perhaps they had an inhibitory role against V. parahaemolyticus. Interestingly, there was no Vibrionaceae bacteria found in the shrimps' bodies however a count of 5.5 x 107 CFU/ml of Vibrio bacteria was found from the culture water. It could be possible that, the Pseudomonas spp. from the control group (as a natural micro flora) and B. subtilis for treatment groups played the inhibitory roles against pathogen bacteria or Vibriosis, by action of competitive exclusion or adhesion site.